Identification of Gene Candidates in Diterpenoid Biosynthesis of Curcuma longa: An mRNA Sequencing Approach: Identification of Gene Candidates in Diterpenoid - Fadhullah, Hafizh; Purwoko, Devit; Zulaeha, Siti; Hanifah, Nurul Fitri; Hartuti, Endah Dwi; Rahmadara, Gemilang; Safarrida, Anna; Reninta, Rikania; Evawati, Evawati; Roza, Irwan; Tajuddin, Teuku (Journal of Tropical Life Science, 2024)
Curcuma longa is a medicinal plant renowned for its therapeutic properties and potential treatment of cancer. This study focused on the biosynthesis of diterpenoids in the rhizome and leaves of C. longa. The genes responsible for producing these medicinal compounds were analyzed using BLASTx, Gene Ontology (GO) annotation, differential expression, and homology. The substantial dataset was obtained from the National Center for Biotechnology Information (NCBI), comprising 151,730,334 clean reads and 167,264 transcripts for the analysis. The results of the BLASTx analysis were as follows: NR yielded 65.93%, Swiss-Prot yielded 44.52%, and COG yielded 17.35%. Subsequently, GO annotation was performed using Blast2GO, resulting in an annotation rate of 56.79%. Differential expression analysis revealed a total of 636 genes that were significantly differentiated between the rhizome and leaves. The homology analysis resulted in 11 proteins associated with diterpenoid biosynthesis and nine proteins related to CYP450. Approximately three class I proteins were highly expressed in the rhizome. Additionally, seven CYP450 enzymes from the CYP71D and CYP726 subfamilies were identified; three were highly expressed in the rhizome. The expression patterns of these enzymes were similar to the aforementioned three class I diTPSs, indicating their potential involvement in macroditerpenoid biosynthesis in C. longa. These findings provide valuable genomic resources for future functional genomics research on C. longa, facilitating targeted efforts to enhance the production of bioactive compounds.